2021
DOI: 10.21608/ejaj.2021.183231
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pests and Pathogens Affecting Citrus Yield in Egypt with Special Emphasis on Nematodes

Abstract: Although citriculture ranks high in Egypt as a superior orange producer and exporter country, citrus yield should be further optimized via management of pests and pathogens that adversely affect citrus orchards. We throw light on the various groups of these citrus-damaging organisms to alarm for the significance of adopting adequate programs for their control. As many plant-parasitic nematode (PPN) species in Egypt and abroad; all but one, the citrus nematode Tylenchulus semipenetrans, of which are of limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The citrus slow decline nematode, T. semipenetrans, is one of the main biotic stress factors for yield loss in citrus orchards around the world (O'Bannon & Hutchinson 1974;Bello et al 1986;Duncan & Cohn 1990;Duncan 2009;Hammam et al 2021). The present survey confirmed occurrence of this citrus nematode in Hatay, Osmaniye, Adana, and Mersin provinces in the Mediterranean region of Turkey (Table 2).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The citrus slow decline nematode, T. semipenetrans, is one of the main biotic stress factors for yield loss in citrus orchards around the world (O'Bannon & Hutchinson 1974;Bello et al 1986;Duncan & Cohn 1990;Duncan 2009;Hammam et al 2021). The present survey confirmed occurrence of this citrus nematode in Hatay, Osmaniye, Adana, and Mersin provinces in the Mediterranean region of Turkey (Table 2).…”
Section: Discussionsupporting
confidence: 75%
“…1986; Duncan & Cohn 1990; Duncan 2009; Hammam et al . 2021). The present survey confirmed occurrence of this citrus nematode in Hatay, Osmaniye, Adana, and Mersin provinces in the Mediterranean region of Turkey (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence of Meloidogyne spp. was lower than that in Egyptian citrus orchards intercropped with tomato [ 8 ], which implies the decent linkage between these nematodes and citrus crops rather than its presence in intercropped trials with native hosts or in weeds. Several studies recorded in Taiwan and India have reported that Meloidogyne spp.…”
Section: Discussionmentioning
confidence: 99%
“…and Longidorus spp. have been detected in Egypt [ 8 ], Spain [ 12 ], and Tinsukia [ 42 ]. In our study, S. bradys and H. indicus were found at low densities that varied between two and four nematodes per 100 g of soil and between two and seven nematodes per 100 g of soil, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation